A cultura da escola inclusiva na perspectiva dos alunos surdos - Morás, Nadjanara Ana Basso (2018)
The inclusive education has been a theme of global discussion since the 1990s, causing the beginning of perspectives and confrontations of obstacles in its concretization process. The general objective of this study was to investigate the inclusive school culture from the perspective of deaf students who study in the context of regular education. Aside from the bibliographic sources recompiled and read, covered with importance by being able to provide actual and relevant informations, also was held semistructured interviews, with theoretical benchmark in Pierre Bourdieu (2013). The interviews happened in one of the classrooms of the school that has as proposal the bilingual education for deaf. The questions were made in Brazilian signals language (Libras) by the researcher – who has a degree in Mathematics as well as of Translator and Interpreter of Libras/Portuguese -.The interviews were made at the end of June, during July and beginning of August 2016. It is emphasized that in the moment of the interview only the researcher and the interviewed person remained in the room, in order to preserve the anonymity. The participants of this research were deaf students who studied from kindergarten until the elementary school in a school with a proposal of bilingual education for the deaf and that nowadays attend to an inclusive regular school. The participants of this research were deaf students who studied from kindergarten until the elementary school in a school with a proposal of bilingual education for the deaf and that nowadays attend to an inclusive regular school. Therefore, the results obtained along the research presented difficulty in the participants’ inclusion development based on the respect for their cultural and linguistic differences, in the inclusive state school, since the school did not reach to overcome the tendency of a homogenization culture present in the “school culture”. Thus, for inclusion of deaf students in the school environment, it is fundamental to adapt this environment so that the individuals in question feel part of a whole. It is necessary to elaborate the inclusion as a broad process, with ideological, social, cultural, political and economic dimensions, involving all the interpersonal relationship existing in the school and outside it. It is considered necessary to be cautious so that school inclusion is not caught in the trap of standardization, or rather, in the deaf student’s inclusion in the mainstream education being the sign language seen as a set of facilitating codes of communication, as teaching instrument, disregarding the cultural nature present in Libras